2017
DOI: 10.1038/labinvest.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

The kinesin KIF14 is overexpressed in medulloblastoma and downregulation of KIF14 suppressed tumor proliferation and induced apoptosis

Abstract: Medulloblastoma (MB) is the most common malignant brain tumor in childhood. At present, there is no well-established targeted drug for majority of patients. The kinesin family member 14 (KIF14) is a novel oncogene located on chromosome 1q and is dysregulated in multiple cancers. The objectives of this study were to evaluate KIF14 expression and chromosome 1q copy number in MB, and to delineate its biological functions in MB pathogenesis. By quantitative RT-PCR and immunohistochemistry, we found KIF14 was overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Yang et al linked the upregulation of KIF14 in GC to poor prognosis, suggesting that it could play a critical function in GC pathogenesis ( Yang et al, 2019 ). In addition, KIF14 has been reported to serve oncogenic roles in a variety of malignancies such as colorectal cancer ( Wang et al, 2018 ), medulloblastoma ( Li et al, 2017 ), cervical cancer ( Wang et al, 2016 ). Moreover, KIF15 played a critical role in inhibiting GC cell apoptosis and promoting cell proliferation, and the high expression of KIF15 predicts a poor prognosis in GC patients ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al linked the upregulation of KIF14 in GC to poor prognosis, suggesting that it could play a critical function in GC pathogenesis ( Yang et al, 2019 ). In addition, KIF14 has been reported to serve oncogenic roles in a variety of malignancies such as colorectal cancer ( Wang et al, 2018 ), medulloblastoma ( Li et al, 2017 ), cervical cancer ( Wang et al, 2016 ). Moreover, KIF15 played a critical role in inhibiting GC cell apoptosis and promoting cell proliferation, and the high expression of KIF15 predicts a poor prognosis in GC patients ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We further examined SETD2 and H3K36me3 levels by immunohistochemistry in our cohort. We adopted a semiquantitative scoring system in which signal intensity and percentage of positive cells were considered as parameters in grading IHC staining result . We found SETD2 expression level was not significantly different between SETD2‐wild‐type and SETD2‐mutant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, KIF14 expression was found to be significantly elevated in 7 medulloblastoma cell lines and 32/32 human medulloblastoma tumor samples [64] . Analysis on a separate group of 93 medulloblastoma samples demonstrated that, as in glioma, greater KIF14 expression corresponded to shorter progression-free survival and overall survival.…”
Section: Kif14 Is Mutated In Primary Microcephaly and Upregulated mentioning
confidence: 99%